Strengthening quality care in professional alternative child and youth care in group homes through continuing professional development - Monika Lengauer; Christian Posch (Scottish Journal of Residential Child Care)
Between February 2021 and December 2022, a large-scale project developed the ‘curriculum for the dual practice-oriented continuing professional development for professionals in professional alternative child and youth care in group homes’ in Austria (FICE Austria, 2023). The project was initiated by FICE Austria. Sixteen experts from 20 organisations across Austria took part in developing the curriculum. It aims to further the development of the quality of care in professional alternative child and youth care settings in Austria. Existing and recognised training courses can only qualify professionals for alternative child and youth care settings to an extremely limited extent. This article presents the need for development and presents the cornerstones of the curriculum.